Radical Scavenging Potential of Ginkgolides and Bilobalide: Insight from Molecular Modeling - Davide Zeppilli; Giovanni Ribaudo; Nicola Pompermaier; Andrea Madabeni; Marco Bortoli; Laura Orian (MDPI AG, 2023)
The reactive oxygen species (ROS) scavenging capacities of ginkgolides and bilobalide, which are the peculiar constituents of the extract of Ginkgo biloba, are investigated in silico (level of theory: (SMD)-M06-2X/6-311+G(d,p)//M06-2X/6-31G(d)). Unlike other popular antioxidant natural substances, the carbon backbones of these compounds are entirely aliphatic and exclusively single C-C bonds are present. The selectivity for alkoxyl radicals via hydrogen-atom transfer (HAT) is assessed; importantly, the scavenging of peroxyl radicals is also possible from a peculiar site, here labeled C10 both for ginkgolides and bilobalide. The energetics are described in detail, and the analysis discloses that the studied compounds are powerful scavengers, with thermodynamic and kinetic properties similar to those of Trolox and melatonin, and that, in addition, they display selectivity for peroxyl radicals. These are all chemical-reactivity features contributing to the therapeutic action of the extract of G. biloba.